THE MAIN TRENDS IN THE DEVELOPMENT OF TERMS RELATED TO PEDAGOGY IN COMPARATIVE LANGUAGES - Nizomova Mokhinur Baratboyevna (International Scientific and Current Research Conferences, 2024)
In the past two decades, there has been active work on ordering and systematization of pedagogical terminology. She made it possible to designate a list of problems that require their own solutions. These include the following: ambiguity pedagogical terms, duplication of English pedagogical terms in foreign languages, the introduction of new words into scientific circulation, pretending to be terms without connection with a specific concept and phenomenon, etc. One of the main ways to solve these problems there is an active lexicographic activity in the field pedagogy. Ordering and systematization of pedagogical terminology possible only on the basis of a serious study and understanding of the entire the history of the formation and development of pedagogical terminology and taking into account the traditions of the Uzbek language. One of the priority areas of such work should be the preparation of a historical terminological pedagogical dictionary.